Dynamics of Campaign Reporting and Press-Party Parallelism: Rise of Competitive Authoritarianism and the Media System in Turkey. (4th May 2021) - Yıldırım, Kerem; Baruh, Lemi; Çarkoğlu, Ali
ABSTRACT: How do press-party parallelism dynamics unfold in media systems that experience competitive authoritarianism? We analyze the content of news coverage of political parties across four consecutive national election campaigns in Turkey (2002, 2007, 2011, and 2015) to track changes in press-party parallelism. We explore three dimensions of press-party parallelism in order to study its dynamics: visibility of political parties, the effective number of parties represented in newspapers, and lastly, favorability toward political parties. First, within each campaign cycle, as election day approaches, visibility of the incumbent party increases while the visibility of other parties tends to decline. Likewise, the incumbent party's visibility increases across the four elections we study. Second, for all newspaper groups, the number of parties that receive favorable or unfavorable coverage declines over consecutive election terms. Third, the incumbent party is the only that gains in terms of positive coverage within and across each election campaign period. Taken together, we show evidence for press-party parallelism dynamics in a competitive authoritarian country.